MANGGARAI STATIONâS INTERIOR DESIGN REVITALIZATION THROUGH MODERN DESIGN - Safiera, Amanda
The Manggarai Station’s interior revitalization project are selected from a main issue of citizen’s lack appreciation towards historical places and national cultural heritage. It all happened because they’re to busy to adapt with transition in mass transportation system and also transformation era. Therefore, most of them are not considerate and unaware about the historical sites around them—even the ones they made contact everyday. Manggarai Station has the largest railway and the busiest station in Indonesia. Hence, this project will applying modern design elements to upgrade the Manggarai building’s historical value. In addition to historical and architectural aspects, the design will also consider the importance of upgrading the functional aspect of a train station, such as organize and controlling visitors behavior while using station facilities. The modern design will require some certain characteristics like simple, clear, and accessible for any kind of passenger, with the result of secure athmosphere, comfrotable, along with historical value that live on Manggarai Station environment. There are two methods for gathering information that are used in this project, that is field observation/survey and literature studies. Field bservation are tend to rely on observer’s ability to understand and evaluate the existing’s qualitative aspects. The intention is to observe directly through the characters or the behaviors of the passengers, their activities, interior ambience conditio, and also inspect the common issues that are going on the station. In literature studies , the method is to gather and search for references or basic theory that are related to the issues from observing activity, or maybe from design process. This method are requiring valid literature from articles, books, journals, and websites. Aside from gathering informations, analysis method are also used by comparing datas from official, trusted literature and from field observation’s result—to search the main problem to be solved. Because it’s lacking in “serving” the heritage objects makes people are losing their interest in them, using the strategy by applying modern design onto the station’s facilities can help to develop the potential values of the conservated building. This strategy are expected to create new, optimal experiences toward the station passengers, so that public mass can interact directly with those historical objects. Also, the historical values from the building can also be preserved through interior design approaches.